Pengembangan Sistem Kontrol Mesin CNC Training Unit 3 Axis - Salam, Abdul; Rasyid, Syaharuddin; Alim, Ahmad; Uswat Hasnan, A.; Khalid, Khalid (Politeknik Negeri Ujung Pandang, 2025)
This research aims to upgrade the TU-3A CNC machine control system using the Mach3 microcontroller so that it can improve the feeding shape that is able to support CAD CAM technology, Measure and analyze the precision of the machine axis movement, Calculate and analyze the cost of developing a 3 Axis CNC Training Unit machine control system. This research was conducted through several stages of literature study, design, overhaul, manufacture, assembly, testing and data analysis. The research method carried out is upgrading the control system by changing the control system using a Mach3 microcontroller, measuring and analyzing and analyzing the precision of the machine axis movement with a dial indicator measuring instrument and a 0.05 accuracy caliper. The material used for testing is soft material such as Teflon, aluminum and acrylics, with the results showing that the TU-3A CNC machine can produce products with the expected precision. The conclusion of this research has resulted in the development of a 3 Axis CNC Training Unit machine using a Mach3 microcontroller so that it can improve the shape of the feed that is able to support CAD CAM technology and produce products from acrylic and aluminum materials. Measurement and analysis of data testing the precision of the machine axis movement, it is known that the deviation in the X, Y, and Z axes on the TU-3A Mach3 CNC machine is smaller than the deviation on the TU-3A EMCO CNC machine.